Exchange Rate Pass-Through in the Euro Area : The Role of Asymmetric Pricing Behavior - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 2004)
Exchange rate pass-through in a set of euro area prices along the pricing chain is examined. Using a vector autoregression (VAR) approach, the empirics analyze the joint time-series behavior of the euro exchange rate and a system of euro-area prices in response to an exchange rate shock. The impulse-response functions from the VAR estimates are used to identify-in a 'new open economy macroeconomics model'-those key behavioral parameters that best replicate the pattern of exchange rate pass-through in the euro area. Area-wide prices are found to display incomplete pass-through, consistent with euro currency-pricing and pricing-to-market behavior. The results are compared to those for the other major industrial economies, and suggest that, as with the United States, "expenditure-switching" effects on the current account still operate but are generally small.